Efecto de condiciones de tostado en dos variedades de cacao sobre las propiedades fisicoquímicas y sensoriales del licor - Barberan Macías, Anggie Melissa (2023)
The aim of the research was to evaluate roasting conditions (temperature-time) in two cocoa varieties. A completely randomized design (CRD) was applied with two study factors: Factor A roasting conditions with the levels (130°C x 60 min, 140°C x 60 min, 130°C x 70 min, 140°C x 70 min) and factor B two varieties of cocoa (CCN-51 and Cacao Fino y Aroma). Eight treatments were obtained and three replicates were made, resulting in 24 experimental units of 2 kg. The physicochemical variables evaluated were: moisture and testa (before roasting), ash and fat (after roasting). Sensory attributes were evaluated: cocoa, floral, fruity, nutty, caramel, basic flavors (bitter, acidity, astringency) and aroma (floral, fruity). The physicochemical results were as follows: For the moisture variable, no level complied with INEN 176 standards. For the testa variable, level b1 obtained the lowest percentage with 13.90%, which is within the standard. After roasting in the liquor, the highest percentage of ash was in treatment T2 with 3.59%, which complies with NTE. INEN 623, in the percentage of fat the roasting condition a1 and a4 obtained the highest percentages with 51.6917% and 52.2283%. In sensory terms, it was evident that the best treatment that obtained superior characteristics was T5. This indicates that the best roasting condition was 130°C x 70 min in the CCN-51 variety.